Implementation of E-Government through UMKM Clustering in Improving Digitalization in Kutai Timur Regency - Reza Laksana Putra; Dirk Malaga Kusuma; Munawaroh Munawaroh; Andi Nurhayati; Kayla Adinda Utomo (Dinasti Publisher, 2026)
The Local Government has created a digital-based UMKM clustering with the aim of facilitating transactions for the community and business actors to enhance the regional economic turnover. This research uses a descriptive qualitative method. This research uses secondary data sources from various trusted sources, including official government documents, scientific journal articles, and case studies on the implementation of digitalization in the public sector. In addition, literature analysis also helps in identifying the challenges faced. The data collection techniques in this study are observation, interviews, and documentation. In this study, the data analysis technique uses the data analysis model according to Miles et al. (2019), which includes data collection, data condensation, data display, and conclusion drawing and verification. The purpose of this research is to assess the implementation of e-government through the UMKM website in East Kutai Regency in enhancing digitalization. This study also identifies the obstacles faced in the implementation of this website, as well as analyzes the role of the local government in the success of UMKM digitalization. The conclusion that can be drawn from this research is that the implementation of e-government is progressing well.